Social Construction of Young Married Couples in Parenting Children in South Jakarta - Syamsiah; Adisa Cahya Rianti (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2022)
In married life or household life, children are a gift and gift given by God to complete the happiness of parents. Until now, we still meet couples who get married at a young age. Many of them are actually not ready to have children, thus allowing them to provide inappropriate parenting. The purpose of this study was to determine and understand the social construction of young married couples in South Jakarta in deciding to marry and raise children. This research is a research with qualitative methods using interactive analysis techniques including data reduction, data presentation to draw conclusions. The results of the study indicate that the social construction of young married couples in raising children in South Jakarta is not quite good and well-constructed. There is no readiness of couples to raise children and young married couples in South Jakarta are trying to improve their parenting methods by studying parenting or parenting.